Perubahan Kadar Hemoglobin Pada Ibu Hamil Trimester III Dan Sesudah Inpartu 2 Jam Post Partum - Kiswati (LPPM Universitas dr. Soebandi, 2019)
The incidence of anemia in Jember in 2012 reached 40%. Incidence of anemia in pregnant women will increase the risk of maternal death than women who are not anemic, therefore the need for monitoring of hemoglobin levels in early pregnancy to childbirth .This study aims to determine the changes in hemoglobin levels in pregnant women after the third trimester inpartu. Design used in this study using two sample paired comparisons, the data is interval with a descriptive approach. Samples in this study were 30 samples using random sampling techniques. Results of processing of the data showed a hemoglobin level of pregnant women before the third trimester inpartu average of 11.1867% and after inpartu average of 9.1567%, found the average yield of 2.03%. After analyzing the data using two independent samples t test where t count> t table (26.663> 2.000). Ho denied means there is a change in hemoglobin levels in pregnant third trimester and after inpartu. The change of decrease in hemoglobin levels is recommended to overcome early anemia or prior to pregnancy by consuming iron tablets during pregnancy and maternal diet should be well-balanced nutrition is such a material containing iron from animal food (meat, fish, chicken, eggs, liver) and vegetable material (dark green vegetables, beans, tempe) and consuming vegetables (katuk leaves, cassava leaves and spinach) and fruits like tomatoes, oranges and pineapples are very useful to enhance iron absorption in the intestine and pregnant women should hemoglobin levels checked at least once in the third trimester.